Catastrophic right-sided Candida empyema from spontaneous esophageal perforation. (2021) - Jahangir, Abdullah; Sahra, Syeda; Anwar, Shamsuddin; Mobarakai, Neville; Jahangir, Ahmad
Abstract: Right-sided empyema secondary to esophageal rupture are rare but reported in the medical literature. We describe an atypical CASE of right-sided empyema with Candida Tropicalis, Candida Glabrata, and Staphylococcus lugdenensis leading to a diagnosis of spontaneous esophageal rupture. We concluded that pleural effusion with fungal and multi-organism growth should immediately raise suspicion for underlying missed esophageal perforation. Prompt diagnosis of esophageal perforation can prevent fatal complications like pleuritis, pneumothorax, hydrothorax, pneumomediastinum, mediastinitis, acute respiratory distress syndrome, and septic shock.